Malawi : Technical Assistance Report-Public Investment Management Assessment (PIMA). (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance report assesses the state of public investment management (PIM) in Malawi. Measured against the overall strength of its PIM institutions, Malawi performs broadly in line with other low-income developing countries and sub-Saharan African countries, but less well than better-performing emerging markets. Measures of institutional strength show how well Malawi rates in terms of its existing laws and regulations, as well as the formal guidelines and instructions issued by the government to implement these laws. The public investment management assessment diagnostic tool also measures how effectively, in practice, the government implements and enforces these laws and regulations. On this measure of effectiveness, Malawi performs relatively poorly. Looking at individual indicators of PIM, Malawi's performance is mixed.